Sjelesorg som flerfoldig og flerstemmig praksis: En porøs innsirkling av sjelesorgen med et interkulturelt blikk (Nordic Journal of Practical Theology, 2020)
This article aims to circumscribe pastoral care as a porous practice that is intertwined with other practices and takes place in congregational rooms, as well as in public spaces. By relating empirical research, theories, and experiences from Nordic countries to theories from the intercultural paradigm, we explore a multifaceted and multivoiced practice of pastoral care. Grounded in fieldwork, empirical material, and newer pastoral care theory, we argue that contemporary pastoral care should emphasize the relevance, importance, and necessity of social, cultural, gender, racial, ecological, and political issues, to a higher degree than earlier Nordic literature may suggest.